Self-reported Confidence of the Dental Faculty Participants of “Training Workshop on Objective Structured Clinical Examination (OSCE)” - Piryani, Rano Mal; Piryani, Suneel; Sharma, Nitasha (Janaki Medical College Journal of Medical Science, 2020)
Background and Objectives: Objective Structured Clinical Examination (OSCE) is one of the assessment tools used to assess the clinical skills. Health Professions Training Committee (HPTC), Universal College of Medical Sciences (UCMS), Bhairahawa, Nepal organized 2-days Training Workshop on OSCE in Feb 13-14, 2020 for dental faculty. The objective of this study was to assess the feedback of the participants of training workshop on OSCE and their self-reported confidence using retro-pre-questionnaire. Material and methods: The feedback was taken on the pretested semi-structured questionnaire comprised of four parts: A. Demographic Information, B. Overall feedback on the training workshop- (closed-ended questions), C. Feedback on specific sessions conducted in the training workshop on retro-pre-questionnaire and D. Feedback on good points/strengths of the raining workshop and areas for improvement- (open-ended questions). Analysis was done with SPSS-21. Results: The rating of the participants on training workshop for usefulness, course content of training, relevance of session & content, facilitation and overall was notable. Participants’ self-reported confidence remarkably enhanced after participation in the training workshop(before vs after)on all four skills; develop blueprint for the assessment (1.33±0.5 vs 3.33±0.50), develop blueprint and test map for OSCE (1.22±0.44 vs 3.11±0.33), develop OSCE station (33±0.70 vs 3.67±0.50) and conduct OSCE examination (1.22±0.67 vs 3.33±0.50). Participants stated “the training workshop was interactive and participatory” and suggested to include more dental related tasks in training. Conclusion: Overall the feedback of the participants was positive and noteworthy. Participants’ self-reported confidence remarkably enhanced after participation in the training workshop.